Pemberdayaan Remaja Desa Tahunan Kecamatan Sale Kabupaten Rembang dengan Keterampilan Karawitan, Dalang dan Seni Tari Sebagai Upaya Mengurangi Angka Kemiskinan - Muhammad Tahwin; Dian Anita Sari (Journal of Dedicators Community, 2019)
These community service activities are carried out in the Tahunan Village, Sale District, Rembang. The existence of arts groups in the village still requires assistance from human resource such as trainer. Therefore, this service aims to 1) strengthen the position of the arts group to be more empowered; 2) increasing the number of group members from young people; 3) improve the skills of group members in musical, orchestrating, and dancing; and 4) increase the income of group members. The method used in this community service program is training and mentoring. The results of this program are: 1) The arts group already has a name and routinely conducts meetings and training activities; 2) members of group from the school age and young adults are increasing; 3) the art group is known outside the Sale District and gets a performance offer.